Classification, Diagnosis, and Treatment of Syncope - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The classification, diagnosis, investigation, and management of syncopal attacks in childhood are reviewed from the Department of Cardiology, Royal Hospital for Sick Children, Glasgow, UK.